PERANCANGAN SISTEM INFORMASI AKUNTANSI KAS KECIL (PETTY CASH) DI PT. KOPRIMA SANDYSEJAHTERA - Nathaniela Febrianti; Muthmainnah; Candra Mecca Sufyana (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2023)
Petty cash is a company-provided fund for operational activities with a relatively small nominal amount. When processing petty cash at PT. Koprima Sandysejahtera still uses Microsoft Excel, which makes the company's performance less effective in managing petty cash. Therefore, the authors designed a web-based cash accounting information system with the programming language PHP and My SQL as a database. The research method used is qualitative. Data and information were obtained through observation, interviews, documentation, and literature research. The software development method used is the waterfall model, where the phases from system analysis to system maintenance are sequential and cannot be done randomly. With the existence of a computerized system, the company's performance in terms of petty cash management is expected to become more effective.